Predictive equations of maximum respiratory mouth pressures: a systematic review - Souto-Miranda, S. (2020)
Background Maximum inspiratory (Pimax) and expiratory (Pemax) mouth pressures are commonly used to detect respiratory muscle weakness resorting to predictive equations established for healthy people. There are several predictive equations, but they are widespread in the literature. This study aimed to review the existent predictive equations of maximum inspiratory (Pimax) and expiratory (Pemax) mouth pressures for adults. Additionally, we aimed to identify which ones were generated based on international standards. Methods A systematic review of predictive equations of Pimax and Pemax for healthy adults was conducted. A comprehensive search was performed of Cochrane Library, EBSCO, PubMed, Scopus and Web of Science to identify studies that presented at least one equation for Pimax or Pemax developed for healthy adults. The quality of studies was assessed by two reviewers with the Quality Assessment of Diagnostic Accuracy Studies (Quadas-2). Results Risk of bias was high in 8 of the 20 studies included. Forty-two Pimax and 34 Pemax equations were found, mostly using the variables age (n = 39), weight (n = 20) and height (n = 8). These equations explained 3 to 96% of the Pimax/Pemax variance. They were developed with individuals from 11 countries (Portugal not included). Twelve Pimax and eight Pemax equations complied with international standards. Conclusions This review gathered the predictive equations that have been developed for both Pimax and Pemax, however most were generated from unstandardized procedures. Future studies should explore the suitability of these equations for populations for which specific ones are not available, such as the Portuguese population, and develop new equations if necessary.